MELASMA SHOW UP IN CONTRACEPTIVE PILLS ACCEPTORS - Cahya Novenita Azzahra; Widyawati Widyawati; Liza Afriliana; Julian Dewantiningrum (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
AbstractIntroduction : Melasma is one of the most common hyperpigmentation disorders among womans, the common hyperpigmentation patches which commonly found on face especially on sunlight exposured area. One of the factors causing melasma is the use of oral contraceptives which cause the buildup of the hormones estrogen and progesterone on the skin.Objectives : Thus, the aim of the study is to analyze the association between duration of contraceptive pills use and melasma.Methods : This study used a cross-sectional design. The research was conducted in May-July 2020. The subjects were 36 womans aged 30-55 years old and oral contraceptive acceptors that qualify inclussion criteria and not eligible exclussion criteria. The data was collected primarily using questionnaires. Physical examinations were done through observation with a photo of the respondents. Data analysis using the Chi Square test with a significance value p <0,05.Results : Based on the results of this study, the significance of 0.017 less than 0.05 which indicates a relationship between variables duration of contraceptive pills use and melasma. Conclusions : This study shows a association between duration of contraceptive pills use and melasmaKeywords : melasma, contraceptive pills.